Características da resposta imune em pacientes com leishmaniose tegumentar americana, antes e após tratamento quimioterápico com antimonial pentavalente - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The installation process of leishmaniasis in the host is determined by a complex association between factors related to virulence of the parasite and the host immune response. Factors such as parasite species, its virulence and tropism, besides the genetic condition and host immune trigger different clinical forms in American cutaneous leishmaniasis (ACL). As a result, it is of paramount importance to understand the mechanisms of the immune response against the parasite, cell types, cytokines and response profile involved in this process, since these factors may confer some resistance to the parasite and/or prevent the development reinfection. 33 patients with ACL caused by Leishmania (Viannia) guyanensis, L. (V.) naiffi and L. (Leishmania) amazonensis. The predominant species found was L. (V.) guyanensis representing 73% of cases. The comparative analysis of the cellular and cytokine profile evaluated by the techniques of flow cytometry and ELISA in infected patients was significantly higher than in individuals without infection (control). Apparently, the infection caused by L. (V.) guyanensis induces a higher concentration of pro-inflammatory cytokines (IL-2 and INF-γ) than infection caused by L. (L.) amazonensis, what was not observed in infection by L. (V.) naiffi. There was variation in the concentration of cytokines and cell percentage in samples from infected patients before initiating treatment with pentavalent antimony compared to the control group and after treatment. The percentage of CD4+ T cells prior to treatment was greater than CD8+ T cells. Lower percentage of regulatory T cells was observed before treatment. These results indicate that there is influence of immune response modulation on Leishmania infection and infections caused by L. (V.) guyanensis have exacerbated the response to infection caused by the other species studied here.
Keywords: Leishmaniose; Marcadores Celulares.; Leishmaniasis; Cell Markers.; CIÊNCIAS BIOLÓGICAS